2017
DOI: 10.7717/peerj.3659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental noise and music on dexmedetomidine-induced sedation in dogs

Abstract: BackgroundPrevious studies in human patients suggest depth of sedation may be affected by environmental noise or music; however, related data in domestic animals is limited. The objective of the current study was to investigate the effect of noise and music on dexmedetomidine-induced (DM- 10 µg/kg, IM) sedation in 10 dogs.MethodsIn a crossover design, post-DM injection dogs were immediately subjected to recorded human voices at either 55–60 decibel (dB) (Noise 1) or 80–85 dB (Noise 2); classical music at 45–50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 40 publications
0
17
0
8
Order By: Relevance
“…While substantial evidence has been shown that music can benefit animal welfare by decreasing anxiety and performance of stress-related behaviors, these effects did not carry over to the sedated patient. 13 Albright et al discovered that, while noise over 80 dB, which is similar to that found in a veterinary clinic, was detrimental to sedation and increased spontaneous behavior scores, music did not positively impact sedation. 13 These findings beg the question whether music, specifically cat-specific music, can provide similar outcomes in cats.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…While substantial evidence has been shown that music can benefit animal welfare by decreasing anxiety and performance of stress-related behaviors, these effects did not carry over to the sedated patient. 13 Albright et al discovered that, while noise over 80 dB, which is similar to that found in a veterinary clinic, was detrimental to sedation and increased spontaneous behavior scores, music did not positively impact sedation. 13 These findings beg the question whether music, specifically cat-specific music, can provide similar outcomes in cats.…”
Section: Introductionmentioning
confidence: 77%
“…13 Albright et al discovered that, while noise over 80 dB, which is similar to that found in a veterinary clinic, was detrimental to sedation and increased spontaneous behavior scores, music did not positively impact sedation. 13 These findings beg the question whether music, specifically cat-specific music, can provide similar outcomes in cats. In fact, Snowdon and Teie recently concluded that cats listening to music in their homes prefer music that was specially made with cat vocalizations, with preferred tempos and with normal vocal frequencies as the primary considerations.…”
Section: Introductionmentioning
confidence: 77%
“…Overall, classical music was associated with dogs spending more time sitting or lying down, resting and sleeping, and less time vocalizing and standing ( Table 1). However, music marketed as being specifically designed for dogs (the five studies examining dog music all used "Through a dog's ear") did not appear to have many beneficial effects over and above those gained by exposing dogs to a random selection of classical music [14][15][16]18,20]. This is likely due to the heterogeneity of the populations studied, and/or a lack of sensitivity in the response variables measured.…”
Section: Discussionmentioning
confidence: 98%
“…Exposure to classical music has been shown to enhance immune function and anti-tumor responses in laboratory rodents (both mice and rats) [21], and immunity and developmental stability in layer chicks [23]. Investigations into the effects of the exposure of veterinary patients to music in clinics have begun [16,18,20], but such studies have thus far been limited by small sample sizes. Another potential use of music in animal shelters is to influence animal movement patterns [8,24] by drawing towards certain areas and repelling them from others.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory stimulation has also been tested in veterinary hospital settings, in anaesthetised dogs [ 13 ] and cats ( Felis catus ) [ 14 ]. Dogs were exposed to human voices at two different volumes, bespoke music specifically designed for dog relaxation and background noise (positive control), all of them + a dexmedetomidine (DM) injection.…”
Section: Introductionmentioning
confidence: 99%